Comparison of the histamine hypersensitivity and the Limulus amoebocyte lysate tests for endotoxin activity. - Munoz, J J (1978)
The histamine hypersensitivity test and the Limulus amoebocyte lysate test were compared for their effectiveness to quantitate endotoxin activity. The two tests compared favorably in all the trials, except with a sample of endotoxin from Brucella abortus that gave a positive Limulus amoebocyte lysate test at a concentration of 0.001 microgram, while failing to sensitize mice to histamine at a dose of 16 microgram per mouse. The Limulus amoebocyte lysate test was more sensitive than the histamine hypersensitivity test.